Cannabinoid Type 2 (CB2) Receptors Activation Protects against Oxidative Stress and Neuroinflammation Associated Dopaminergic Neurodegeneration in Rotenone Model of Parkinson's Disease - Javed, Hayate; Azimullah, Sheikh; Haque, M. Emdadul; Ojha, Shreesh K. (Frontiers in Neuroscience, 2016)
The cannabinoid type two receptors (CB2), an important component of the endocannabinoid system, have recently emerged as neuromodulators and therapeutic targets for neurodegenerative diseases including Parkinson’s disease (PD). The downregulation of CB2 receptors has been reported in the brains of PD patients. Therefore, both the activation and the upregulation of the CB2 receptors are believed to protect against the neurodegenerative changes in PD. In the present study, we investigated the CB2 receptor-mediated neuroprotective effect of β-caryophyllene (BCP), a naturally occurring CB2 receptor agonist, in, a clinically relevant, rotenone (ROT)-induced animal model of PD. ROT (2.5 mg/kg BW) was injected intraperitoneally (i.p.) once daily for four weeks to induce PD in male Wistar rats. ROT injections induced a significant loss of dopaminergic (DA) neurons in the substantia nigra pars compacta (SNpc) and DA striatal fibers, following activation of glial cells (astrocytes and microglia). ROT also caused oxidative injury evidenced by the loss of antioxidant enzymes and increased nitrite levels, and induction of proinflammatory cytokines: IL-1β, IL-6 and TNF-α, as well as inflammatory mediators: NF-κB, COX-2, and iNOS. However, treatment with BCP attenuated induction of proinflammatory cytokines and inflammatory mediators in ROT-challenged rats. BCP supplementation also prevented depletion of glutathione concomitant to reduced lipid peroxidation and augmentation of antioxidant enzymes: SOD and catalase. The results were further supported by tyrosine hydroxylase immunohistochemistry, which illustrated the rescue of the DA neurons and fibers subsequent to reduced activation of glial cells. Interestingly, BCP supplementation demonstrated the potent therapeutic effects against ROT-induced neurodegeneration, which was evidenced by BCP-mediated CB2 receptor activation and the fact that, prior administration of the CB2 receptor antagonist AM630 diminished the beneficial effects of BCP. The present study suggests that BCP has the potential therapeutic efficacy to elicit significant neuroprotection by its anti-inflammatory and antioxidant activities mediated by activation of the CB2 receptors.